(untitled) (Research in Agriculture Livestock and Fisheries, 2025)
Livestock theft poses a serious threat to rural livelihoods in South Africa, particularly within communal farming systems. This study evaluates the effectiveness of agricultural extension strategies in addressing livestock theft among communal livestock farmers in the Mopani District of Limpopo Province, South Africa. A qualitative research approach was employed, using semi-structured interviews with 300 communal livestock farmers. Thematic analysis was applied to systematically categorize and interpret farmers’ unstructured responses. The findings reveal substantial weaknesses in existing extension practices, including limited farmer engagement, inadequate training of extension officers in livestock security, ineffective communication arising from language barriers, and the low visibility of extension personnel in farming communities. The study identifies several promising strategies, such as context-specific awareness campaigns, the formation of farmer groups to promote collective action, improved accessibility of extension services, and increased government investment in basic security infrastructure. These recommendations provide practical guidance for strengthening policy and extension practice to enhance the effectiveness, inclusivity, and responsiveness of interventions aimed at livestock protection. The study concludes that farmer-centered, inclusive, and adaptive extension strategies are urgently needed to address livestock theft in communal farming contexts. Res. Agric. Livest. Fish. Vol. 12, No. 3, December 2025: 379-397